Abdul Halim and His Movement (1911-1962) Seeking Historical Roots of Persatuan Ummat Islam (PUI) Movement - Wawan Hernawan (International Journal of Nusantara Islam, 2014)
This research aims to reconstruct a movement led by Halim from 1911 to 1962. This is an important task in the global era when every body idolizes a global leader. People should be aware and wise to count a local leader who has a significant role in developing and creating a history of a country. In the era when people tend to be static and fatalistic person, Halim proposed a dynamic and progressive thinking. By applying a historical research method, this research found that Halim’s efforts to find out national identity has been initiated since his young age until he passed away. Halim has significantly contributed to the growing of many other movements led by younger generations after him. Halim has also succeeded in solving local people’s problems particularly on education, dakwa and social problems. The emergence of Persatuan Umat Islam (PUI) organization is a fact of Halim’s efforts and struggles.